2013
DOI: 10.3390/ijms140815376
|View full text |Cite
|
Sign up to set email alerts
|

The L10P Polymorphism and Serum Levels of Transforming Growth Factor β1 in Human Breast Cancer

Abstract: The L10P single nucleotide polymorphism (SNP) is located in the signal sequence of the transforming growth factor β1 (TGFβ1) gene. The proline-encoding (Pro-) allele of this SNP has been associated with an increased breast cancer risk, which has been attributed to the elevated secretion of this TGFβ1 variant observed in vitro and in male subjects. Here we investigated the association of the L10P SNP with serum levels of TGFβ1 in female breast cancer patients and controls. We genotyped the L10P SNP in 276 breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…This polymorphism results in the replacement of leucine with proline at codon 10 of the amino acid sequence. As mentioned above, the 'Pro' allele has been shown to be a high activity allele in comparison to the 'Leu' allele [32]. Therefore, it appears that the higher activity c.29C>T alleles of TGFB1 increase the risk of bladder cancer significantly.…”
Section: Discussionmentioning
confidence: 95%
“…This polymorphism results in the replacement of leucine with proline at codon 10 of the amino acid sequence. As mentioned above, the 'Pro' allele has been shown to be a high activity allele in comparison to the 'Leu' allele [32]. Therefore, it appears that the higher activity c.29C>T alleles of TGFB1 increase the risk of bladder cancer significantly.…”
Section: Discussionmentioning
confidence: 95%
“…The study population has been described in detail in [ 36 , 37 ], and its clinical and histopathological characteristics are shown in Table 1 . 276 consecutive female breast cancer patients and 255 female controls (patients with benign gynecological lesions and healthy females) of European background were enrolled between 2002 and 2004 at the Department of Obstetrics and Gynecology, Medical University of Vienna (MUV), Austria.…”
Section: Methodsmentioning
confidence: 99%
“…In an in vitro study, the allele c.+29C was shown to cause an increase in TGF-␤1 secretion compared with c.+29T [50]. Moreover, it was found that the serum concentration was higher in individuals with c.+29CC genotype than those with the c.+29CT or c.+29TT genotype [46,[52][53][54], and the serum concentration of TGF-␤1 was higher with the c.+74G allele in comparison with the c.+74C allele [54].…”
Section: C+29c > T and C+74g > Cmentioning
confidence: 99%